Plants for the Ancestors: Traditional Knowledge and Beliefs of the Mentawaians on Siberut Island. - Maskota Delfi; Laurens Bakker; Nguyen Thanh Tuan; Johan Weintre (Jurnal Antropologi: Isu-Isu Sosial Budaya)
Plants for the ancestors that entail the traditional knowledge and beliefs of the Mentawaians on Siberut Island, is exclusive traditional knowledge of the indigenous people of Mentawai. Traditional Ecological Knowledge (TEK) is one of the most fascinating knowledge sources and valuable to preserve and explore for future regional importance as many types of ethno botanical products remain unexplored.